PENENTUAN KRITERIA DESAIN PENGEMBANGAN OBJEK WISATA CURUG SINDARO DENGAN METODE PARTISIPATORI ERGONOMI - Ali, Alfanu Zainul; Betanursanti, Ida (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Muhammadiyah Gombong, 2024)
Sindaro Waterfall in Wadasmalang village, Karangsambung district is one of the tourist attractions in Kebumen Regency. Sindaro Waterfall has become a tourist destination for the community because of its unique contour with two levels of waterfall. The current condition of Sindaro Waterfall is unkempt, damaged, and not developing, resulting in a decrease in visitor numbers. Therefore, efforts are needed to develop Sindaro waterfall to increase the number of visitors. The aim of this research: 1). Identifying criteria variables at the Curug Sindaro tourist attraction 2). Structuring criteria for developing the Curug Sindaro tourist attraction. Criteria variable data and structuring criteria for developing the Curug Sindaro tourist attraction were obtained using the Ergonomic Participation method. This research uses the Participatory Ergonomics method. Determining the criteria variables for developing the Curug Sindaro tourist attraction was carried out using a Focus Group Discussion (FGD) involving the village head, management (village), BUMDES, visitors, tourism service, public health office. Next, the criteria data was made into a closed questionnaire and distributed to respondents. Questionnaire results are processed using SmartPLS. The results of data processing show significant sub-criteria results, namely revitalization, homestay, tourist information office, Sindaro waterfall gallery, information boards, direction boards, gazebos, signboards for proper waste disposal, supporting facilities such as (toilets, trash cans, etc.), parking area security, safety explanations, warning boards, fishing tours.